The influence of the Great Recession on the relationship between ecological footprint, renewable energy and economic growth - Bárbara Baigorri; Antonio Montañés; María-Blanca Simón-Fernández (Environmental and Sustainability Indicators)
This paper studies the relationship between ecological footprint, economic growth and renewable energy use in 20 OECD countries from 1990 to 2019, paying special attention to the possible existence of structural changes in this relationship over the period studied. Our results provide evidence supporting the presence of breaks, with the Great Recession playing a very important role. Our analysis identified an initial phase of decoupling between economic growth and ecological footprint, which is accompanied by a negative estimation of the semi-elasticity between renewable energy and ecological footprint. Nevertheless, these patterns are becoming less evident after the Great Recession, which has been revealed as a negative factor for the environment. Our results alert us to the need to maintain the environment policies even in periods of crisis, the only way to guarantee a real transition towards a more sustainable economic growth.